Palladium erosion behavior under low/high local hydrogen recycling in steady state plasmas - Glazunov, G.P.; Volkov, E.D.; Baron, D.I.; Konotopskiy, A.L.; Hassanein, A. (Вопросы атомной науки и техники, 2002)
Sputtering experiments were carried out in steady state plasma of a mirror Penning discharge with cathodes made from hydrogen saturated/non-saturated palladium. For the both cases no difference in erosion behavior was found under hydrogen, helium or nitrogen plasma impact, in contrast to observed earlier erosion behavior of deuterium saturated/non-saturated lithium. Possible reasons are suggested and discussed to explain such erosion behavior.